Brother eagle, sister sky : a message from Chief Seattle - Jeffers, Susan (New York : Scholastic Inc., 1992)
A Suquamish Indian chief describes his people's respect and love for the earth, and concern for its destruction.
Ages 5-8.
edited hb 2015-06-16
Keywords: Seattle, -- Chief, -- 1790-1866.; Indians of North America